The state of food security in Bangladesh : an econometric analysis - Akhter, Yesmin; Rahman, Pk. Md. Motiur (BRAC University, 2013)
The main concern of this paper is to examine the food availability, self-sufficiency rate and food gap situation in Bangladesh. Attempt has been made to estimate food gaps between production and requirement for the last ten years. Future productions of rice and wheat have been forecasted by using appropriate econometric methods such as ARIMA and Holt’s linear smoothing parameter approach. Forecasting of future food grain availability, food grain requirement and food gaps between production and requirement from 2007/08 to 2015/16 has been made. Finally some recommendations which would be helpful for improving the food security situation in Bangladesh have been suggested.